Thermoplastic resin composition as well as preparation method and application thereof
By combining modified hollow ceramic microbeads with thermoplastic resin materials, the existing mahjong plaza materials have been solved, and the thermoplastic resin composition with high wear resistance, sound insulation effect and high surface hardness is achieved, which is suitable for high-performance mahjong plaza shells.
Patent Information
- Application Number
- CN202411656665.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing mahjong materials have high noise, wear resistance, toughness and surface hardness during the shuffling or playing card, making it difficult to meet the needs of low noise and high performance.
The coupling agent and stearate modified hollow ceramic microbeads are combined with acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate and toughening agent to form a high-performance thermoplastic resin composition.
It realizes excellent wear resistance, sound insulation and heat insulation effect of the thermoplastic resin composition, as well as high surface hardness and high impact strength, and is suitable for high-performance mahjong plaque shells.
Smart Images

Figure BDA0005142259830000101 
Figure BDA0005142259830000102 
Figure BDA0005142259830000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a thermoplastic resin composition and a preparation method and application thereof. Background Art
[0002] Mahjong is a game of strategy. Its basic strategy is simple and easy to learn, but there are many variations. The combination of the two pieces varies from person to person, making it one of the most attractive forms of strategy. In April 2017, the International Mind Sports Federation announced that mahjong officially became a world mind sport. Common mahjong tiles are mainly made of ox bones (bone surface and bamboo back), melamine resin, plastic, jade, glass, metal, etc. Among them, melamine resin is often used to prepare mahjong tiles for modern automatic mahjong machines due to its high strength, delicate feel and excellent wear resistance.
[0003] The advantages of automatic mahjong machines are mainly reflected in high shuffling efficiency, good noise suppression effect and anti-cheating. Among them, the mute effect of the mahjong machine is mainly achieved by thickening the flannel inside the mahjong machine for sound insulation, and at the same time cooperating with the design of silencer cover and silencer anti-collision leaf. However, it cannot solve the noise generated by the collision between mahjong tiles during the shuffling process or playing cards, and the wear resistance, toughness and surface hardness of conventional mahjong tiles are relatively low, which needs to be further improved.
[0004] Therefore, developing a thermoplastic resin material with low noise, high surface hardness, high toughness and high wear resistance is an urgent problem to be solved in this field. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a thermoplastic resin composition and a preparation method and application thereof. The thermoplastic resin composition has excellent wear resistance, good sound insulation and heat insulation effects, and high surface hardness and impact strength.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a thermoplastic resin composition, which comprises, by weight, 10 to 40 parts of acrylonitrile-butadiene-styrene resin material, 30 to 70 parts of polymethyl methacrylate, 1 to 10 parts of modified hollow ceramic microspheres and 1 to 20 parts of a toughening agent; the modified hollow ceramic microspheres comprise hollow ceramic microspheres modified by a coupling agent and a stearate.
[0008] Hollow ceramic microspheres are tiny spherical ceramic materials, the main components of which are silicon dioxide and aluminum oxide, and have the advantages of being light, hollow, high-strength, wear-resistant, high-temperature-resistant, and corrosion-resistant. In the present invention, the hollow ceramic microspheres are modified by using coupling agents and stearates, and the coupling agents react chemically with the silicon dioxide surfaces of the hollow ceramic microspheres, which is beneficial to preventing the agglomeration of the hollow ceramic microspheres in the resin matrix and improving the compatibility thereof with the resin matrix. The metal ions in the stearates can react with the metal ions in the hollow ceramic microspheres to undergo ion exchange reactions, thereby effectively reducing the polarity of the metal oxides in the hollow ceramic microspheres, enhancing the interface interaction and compatibility between the hollow ceramic microspheres and the resin matrix, and ensuring the impact performance and good compatibility of the thermoplastic resin composition. appearance, avoiding appearance problems such as silver wire or flow marks; at the same time, greatly improving its surface hardness and wear resistance; acrylonitrile-butadiene-styrene resin material (ABS resin) has high impact strength and good glossiness, and low cost; polymethyl methacrylate (PMMA) is an amorphous transparent material with high mechanical strength, surface hardness and good dimensional stability and easy molding. By compounding ABS resin with PMMA, the impact toughness and surface hardness of the material can be improved; therefore, by compounding the modified hollow ceramic microspheres with acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate and toughening agent, the thermoplastic resin composition has excellent wear resistance, sound insulation and heat insulation, high surface hardness and high impact strength.
[0009] In the present invention, the acrylonitrile-butadiene-styrene resin material is 10 to 40 parts, for example, it can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts or any range between the above values, preferably 15 to 25 parts.
[0010] In the present invention, the polymethyl methacrylate is 30 to 70 parts, for example, it can be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts or the range between any of the above values, preferably 40 to 65 parts.
[0011] In the present invention, the mass percentage of polymethyl methacrylate in the thermoplastic resin composition is ≥30%, preferably the mass percentage of polymethyl methacrylate is ≥45%, and more preferably the mass percentage of polymethyl methacrylate is ≥60%.
[0012] In the present invention, the modified hollow ceramic microspheres are 1 to 10 parts, for example, can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, 7 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts, 8 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts, 9 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts, 10 parts or the range between any of the above values, preferably 4 to 8.5 parts.
[0013] In the present invention, the toughening agent is 1 to 20 parts, for example, it can be 1 part, 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts or any range between the above values, preferably 2 to 18 parts, and more preferably 5 to 15 parts.
[0014] Based on 100 parts by weight of the hollow ceramic microspheres, the total addition amount of the coupling agent and the stearate is 0.05 to 0.85 parts, for example, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.22 parts, 0.24 parts, 0.26 parts, 0.28 parts, 0.3 parts, 0.32 parts, 0.34 parts, 0.36 parts, 0.38 parts, 0.4 parts, 0.42 parts, 0.44 parts, 0. 0.46 part, 0.48 part, 0.5 part, 0.52 part, 0.54 part, 0.56 part, 0.58 part, 0.6 part, 0.62 part, 0.65 part, 0.68 part, 0.7 part, 0.72 part, 0.75 part, 0.78 part, 0.8 part, 0.82 part, 0.84 part or a range between any of the above values; preferably 0.15 to 0.65 part, more preferably 0.2 to 0.6 part.
[0015] Preferably, the mass ratio of the coupling agent to the stearate is 1:(0.3-3), wherein the specific value of (0.3-3) can be, for example, 0.3, 0.35, 0.4, 0.45, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.75, 0.78, 0. 8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.2, 2.4, 2.6, 2.8, 3 or any range between the above values; more preferably 1:(0.5-2.2), more preferably 1:(0.6-2).
[0016] Preferably, the coupling agent includes a silane coupling agent and / or a titanate coupling agent.
[0017] In the present invention, the silane coupling agent includes but is not limited to at least one of vinyl triethoxysilane (A151), vinyl trimethoxysilane (A171), vinyl tri(β-methoxyethoxy) silane (A172), γ-(2,3-epoxypropoxy)propyl trimethoxysilane (KH-560), γ-methacryloxypropyl trimethoxysilane (KH-570), aminoethylaminopropyl trimethoxysilane, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane.
[0018] In the present invention, the titanate coupling agent includes but is not limited to at least one of isopropyl tri(isostearoyl) titanate, isopropyl tri(dioctyl pyrophosphoryl) titanate, di(dioctyl pyrophosphoryl) ethylene titanate, and isopropyl tri(dodecylbenzenesulfonyl) titanate.
[0019] Preferably, the stearate comprises at least one of zinc stearate, calcium stearate or magnesium stearate.
[0020] Preferably, the average particle size of the hollow ceramic microbeads is 5 to 30 μm, for example, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, etc.
[0021] In the present invention, the average particle size of the hollow ceramic microspheres is tested by a laser particle size analyzer.
[0022] Preferably, the apparent density of the hollow ceramic microspheres is 0.2 to 1.2 g / cm 3 , for example, it can be 0.2 g / cm 3 , 0.3g / cm 3 , 0.4g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 wait.
[0023] In the present invention, the apparent density of the hollow ceramic microspheres is measured according to the standard GB / T 1636-2008 "Determination of the apparent density of plastic materials that can flow out of a specified funnel".
[0024] In the present invention, the modified hollow ceramic microspheres are prepared by the following method, which comprises:
[0025] The hollow ceramic microbeads, stearate, coupling agent and solvent are mixed and reacted to obtain the modified hollow microbeads; the solvent includes water; the reaction temperature is 50-55°C and the reaction time is 20-60 minutes; and the reaction also includes washing, filtering and drying steps.
[0026] Preferably, the acrylonitrile-butadiene-styrene resin material includes acrylonitrile-butadiene-styrene resin, or a mixture of acrylonitrile-styrene copolymer and butadiene-acrylonitrile-styrene graft copolymer.
[0027] In the present invention, according to the standard GB / T 3682.1-2018, at 220°C and 10kg, the melt flow rate of the acrylonitrile-butadiene-styrene resin, the acrylonitrile-styrene copolymer and the butadiene-acrylonitrile-styrene graft copolymer is independently 3 to 60 g / 10min, for example, 3 g / 10min, 3.5 g / 10min, 4 g / 10min, 4.5 g / 10min, 5 g / 10min, 5.5 g / 10min, 6 g / 10min, 6.5 g / 10min, 7 g / 10min, 8 g / 10min, 9 g / 10min, 10 g / 10min, 11 g / 10min, 12 g / 10min, 13 g / 10min, 14 g / 10min, 15 g / 10min, 16 g / 10min, 17 g / 10min, 18 g / 10min, 19 g / 10min, 20 g / 10min, 21 g / 10min, 22 g / 10min, 23 g / 10min, 24 g / 10min, 25 g / 10min, 26 g / 10min, 27 g / 10min, 28 g / 10min, 29 g / 10min, 30 g / 10min, 31 g / 10min, 32 g / 10min, 33 g / 10min, 34 g / 10min, 36 g / 10min, 37 g / 10min, 38 g / 10min, 39 g / 10min, 40 g / 10min, 41 g / 10min, 42 g / 10min g / 10min, 7.5 g / 10min, 8 g / 10min, 8.5 g / 10min, 9 g / 10min, 9.5 g / 10min, 10 g / 10min, 15 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min, 35 g / 10min, 40 g / 10min, 45 g / 10min, 50 g / 10min, 55 g / 10min, 60 g / 10min or ranges between any of the above values.
[0028] In the present invention, the mass percentage of the styrene structural unit in the acrylonitrile-styrene copolymer is 5-55%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or the range between any of the above values, and the balance is the acrylonitrile structural unit.
[0029] In the present invention, the mass percentage of styrene structural units in the acrylonitrile-butadiene-styrene resin and the butadiene-acrylonitrile-styrene graft copolymer is independently 5-55%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or the range between any of the above values; the mass percentage of butadiene structural units is independently 10-65%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or the range between any of the above values; the balance is acrylonitrile structural units.
[0030] Preferably, at 230° C., 3.8 kg, the melt flow rate of the polymethyl methacrylate is 1 to 17 g / 10 min, for example, 1 g / 10 min, 1.5 g / 10 min, 2 g / 10 min, 2.5 g / 10 min, 3 g / 10 min, 3.5 g / 10 min, 4 g / 10 min, 4.5 g / 10 min, 5 g / 10 min, 5.5 g / 10 min, 6 g / 10 min, 6.5 g / 10 min, 7 g / 10 min, 7.5 g / 10 min, 8 g / 10 min, 8.5 g / 10 min, 9 g / 10 min, 9.5 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 15 g / 10 min, 16 g / 10 min, 17 g / 10 min or a range between any of the above values.
[0031] In the present invention, the melt flow rate of the polymethyl methacrylate is tested according to GB / T 3682-2000 standard.
[0032] Preferably, the toughening agent includes at least one of acrylonitrile-butadiene-styrene rubber powder, acrylic rubber or silicone rubber.
[0033] In the present invention, the mass percentage of butadiene in the acrylonitrile-butadiene-styrene rubber powder is 55-70%, for example, it can be 55%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70% or the range between any of the above values.
[0034] Preferably, the thermoplastic resin composition further comprises 0.5 to 6 parts of other additives in parts by weight, for example, it can be in the range of 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, any of the above values.
[0035] Preferably, the other auxiliary agents include at least one of an antioxidant, a lubricant or a weathering agent.
[0036] In the present invention, the antioxidant includes but is not limited to hindered phenol antioxidants, phosphite antioxidants, etc.; the hindered phenol antioxidants include but are not limited to tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (antioxidant 1010), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester (antioxidant 1076), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine (antioxidant 1098), etc.; the phosphite antioxidants include but are not limited to tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite (antioxidant 626), etc.
[0037] In the present invention, the lubricant includes but is not limited to at least one of vinyl bisstearamide, erucamide or stearate, preferably erucamide.
[0038] In the present invention, the weathering agent includes but is not limited to one or more of hindered amine light stabilizers, benzotriazole light stabilizers, benzophenone light stabilizers or triazine light stabilizers.
[0039] In the present invention, the hindered amine light stabilizer includes but is not limited to bis-2,2,6,6-tetramethylpiperidinol sebacate (light stabilizer 770), polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (light stabilizer 622), poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitrogen]-hexylidene-[4-(2,2,6,6-tetramethylpiperidinyl)-amino]} (light stabilizer 944), etc.
[0040] The benzotriazole light stabilizer includes, but is not limited to, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-3',5'-dicumylphenyl)benzotriazole, and the like.
[0041] The benzophenone light stabilizer includes but is not limited to 2-hydroxy-4-n-octyloxybenzophenone (UV531).
[0042] The triazine light stabilizer includes but is not limited to 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-octyloxyphenol (UV1164).
[0043] As a preferred technical solution of the present invention, the thermoplastic resin composition includes, by weight, 10 to 40 parts of acrylonitrile-butadiene-styrene resin material, 30 to 70 parts of polymethyl methacrylate, 1 to 10 parts of modified hollow ceramic microspheres, 1 to 20 parts of a toughening agent, 0.3 to 3 parts of a lubricant, 0.2 to 1.2 parts of an antioxidant and 0.5 to 1.5 parts of a weathering agent.
[0044] In the present invention, the thermoplastic resin composition may also be added with other additives as needed, illustratively including but not limited to colorants, antistatic agents (such as ethoxy lauric acid amine, dilauryl phosphate, glycerol monostearate, etc.), coupling agents (such as silane coupling agents, titanate coupling agents, etc.), compatibilizers (such as maleic anhydride grafted acrylonitrile-butadiene-styrene polymers, etc.), flame retardants (such as aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate, melamine derivatives, brominated triazines, decabromodiphenylethane, brominated epoxy, etc.), etc.
[0045] In a second aspect, the present invention provides a method for preparing the thermoplastic resin composition according to the first aspect, the preparation method comprising the following steps:
[0046] The acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate, modified hollow ceramic microbeads and a toughening agent are mixed and extruded to obtain the thermoplastic resin composition.
[0047] Preferably, the mixed material further comprises at least one of a lubricant, an antioxidant or a weathering agent.
[0048] Preferably, the mixing comprises premixing acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate and toughening agent and optional antioxidant and 40-60% of lubricant in formula amount, and then adding modified hollow ceramic microspheres and remaining lubricant for mixing.
[0049] Preferably, the extrusion temperature is 200-260° C., the rotation speed is 300-500 rpm, and the pressure is 1-5 MPa.
[0050] In the present invention, the extrusion is carried out in a twin-screw extruder; the aspect ratio of the twin-screw extruder is (40-44):1.
[0051] In a third aspect, the present invention provides a mahjong tile shell, wherein the material of the mahjong tile shell includes the thermoplastic resin composition according to the first aspect.
[0052] In a fourth aspect, the present invention provides a mahjong tile, wherein the mahjong tile comprises the thermoplastic resin composition described in the first aspect or the mahjong tile shell described in the second aspect.
[0053] In the present invention, the mahjong tiles include hand-shuffled mahjong tiles, machine-washed mahjong tiles, etc.
[0054] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] The thermoplastic resin composition provided by the present invention has excellent wear resistance, sound insulation and heat insulation, high surface hardness and high impact strength by adding hollow ceramic microspheres modified by coupling agent and stearate, and the modified hollow ceramic microspheres are compounded with acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate and toughening agent in specific contents. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] Unless otherwise specified, the materials used in the present invention can be purchased from the market or prepared by conventional methods; the materials used in the present invention are as follows:
[0059] ABS resin: ABS PA-757K, Zhenjiang Chimei;
[0060] AS resin: SAN NF2200 AK, Taiwan Chemical;
[0061] PMMA-1: PMMA SX-304, Suzhou Shuangxiang, at 230°C and 3.8kg, the melt flow rate is 2g / 10min;
[0062] PMMA-2: PMMA CM-207, Chimei, Taiwan, melt flow rate 8 g / 10 min at 230 °C and 3.8 kg;
[0063] PMMA-3: PMMA LG2, Sumitomo Chemical, Japan, melt flow rate 15 g / 10 min at 230 °C and 3.8 kg;
[0064] Toughening agent
[0065] Silicone rubber: MR502, Japan Kanebuchi;
[0066] Acrylic rubber: EM500, LG Chemical of South Korea;
[0067] Antioxidant: a composite antioxidant composed of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1;
[0068] Hollow ceramic microspheres: Shanghai Gerunya Nanomaterials Co., Ltd.; average particle size: 20 μm, apparent density: 0.8 g / cm 3 .
[0069] Preparation Examples 1 to 10, Comparative Preparation Examples 1 to 3
[0070] Preparation Examples 1 to 10 and Comparative Preparation Examples 1 to 3 respectively provide a modified hollow ceramic microsphere, wherein the raw materials for preparing the modified hollow ceramic microsphere include hollow ceramic microspheres and a modifier; based on the mass of the hollow ceramic microspheres as 100 parts by weight, the weight fraction of the modifier and the type and proportion of the modifier are shown in Table 1; wherein, “ / ” indicates that the component is not included in the formula; and “-” indicates that the component is included in the formula.
[0071] The preparation method of the modified hollow ceramic microspheres comprises:
[0072] According to the formula, hollow ceramic microbeads, stearate and coupling agent are placed in a reaction kettle, 0.2% of distilled water by weight of the hollow ceramic microbeads is added, the temperature is raised to 55° C. and then fully stirred in a magnetic stirrer for 40 minutes, then washed with deionized water, filtered, and vacuum dried at 60° C. to obtain the modified hollow ceramic microbeads.
[0073] Table 1
[0074]
[0075] Table 2
[0076]
[0077]
[0078] Examples 1 to 15, Comparative Examples 1 to 8
[0079] Examples 1 to 15 and Comparative Examples 1 to 8 respectively provide a thermoplastic resin composition, and the formula of the thermoplastic resin composition is shown in Table 3 in parts by weight; wherein, “ / ” indicates that the component is not included in the formula; and the preparation method of the thermoplastic resin composition comprises:
[0080] Acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate, toughening agent, antioxidant and 50% of the formula amount of lubricant are premixed for 2 minutes to obtain mixture A; modified hollow ceramic microspheres and the remaining lubricant are premixed for 5 minutes to obtain mixture B, and then mixture A is fed into the main feeding port of a twin-screw extruder, and mixture B is fed into the side feeding port of the twin-screw extruder, and the thermoplastic resin composition is obtained through melting, extrusion and granulation; the temperature of the twin-screw extruder from the feeding port to the die head is 160°C, 210°C, 220°C, 220°C, 230°C, 230°C, 240°C, 240°C, 230°C, 230°C, 230°C, 230°C, the rotation speed of the twin-screw extruder is 400rpm, and the pressure is 3MPa; the aspect ratio of the twin-screw extruder is 44:1, and the side feeding port is located at the position of 3-4 screw barrel sections before the die head.
[0081] Table 3
[0082]
[0083]
[0084] Table 4
[0085]
[0086]
[0087] Table 5
[0088]
[0089]
[0090] Performance Testing
[0091] (1) Izod notched impact strength: The notched Izod impact strength of the thermoplastic resin compositions provided in Examples 1 to 15 and Comparative Examples 1 to 8 was tested in accordance with GB / T 1843-2008, “Determination of Izod Impact Strength of Plastics”.
[0092] (2) Hardness: The hardness of the thermoplastic resin compositions provided in Examples 1 to 15 and Comparative Examples 1 to 8 was measured according to Rockwell hardness HRA.
[0093] (3) Wear resistance: The thermoplastic resin compositions provided in Examples 1 to 15 and Comparative Examples 1 to 8 were injection molded to obtain square plates of 3 mm×100 mm×100 mm. The mass change of the square plates before and after wear was tested using an abrasion tester. The test parameters of the abrasion tester were as follows: single arm load: 500 g; grinding wheel model: H-18; sample rotation speed: 60 r / min; number of rotational frictions: 5000 rpm. The smaller the mass change before and after wear, the better the wear resistance.
[0094] (4) Sound insulation: The thermoplastic resin composition is injection molded into mahjong tiles, which are placed in a mahjong machine and shuffled repeatedly. The noise generated by the tiles within 30 minutes is tested using a noise decibel meter, and the maximum noise value is recorded. The smaller the value, the better the sound insulation effect.
[0095] The specific test results are shown in Table 6.
[0096] Table 6
[0097]
[0098] As shown in Table 6, the thermoplastic resin composition provided by the present invention has excellent wear resistance, sound insulation, high surface hardness and high impact strength by adding hollow ceramic microspheres modified by coupling agent and stearate, and the modified hollow ceramic microspheres are compounded with acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate and toughening agent in specific content. It is especially suitable for the shell of injection-molded mahjong tiles, which can effectively improve the problems of scratches and noise caused by the collision of mahjong tiles during shuffling and playing; the cantilever beam notched impact strength of the thermoplastic resin composition is ≥4.5kJ / m 2 , Rockwell hardness ≥109, mass change before and after wear ≤0.48mg, sound insulation effect ≤59 decibels.
[0099] Comparison of Example 1 with Comparative Examples 1 to 6 shows that if specific modified hollow ceramic microspheres are not used or the content of the modified hollow ceramic microspheres is not within a specific range, the toughness or wear resistance of the thermoplastic resin composition is poor, and the sound insulation effect of the obtained mahjong is poor.
[0100] It can be seen from Example 1 and Comparative Examples 7 and 8 that the ABS and PMMA are compounded in specific contents, and the thermoplastic resin composition can have both good toughness and wear resistance.
[0101] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A thermoplastic resin composition, characterized in that The thermoplastic resin composition comprises, by weight, 10 to 40 parts of acrylonitrile-butadiene-styrene resin material, 30 to 70 parts of polymethyl methacrylate, 1 to 10 parts of modified hollow ceramic microspheres and 1 to 20 parts of a toughening agent; The modified hollow ceramic microspheres include hollow ceramic microspheres modified by a coupling agent and stearate.
2. The thermoplastic resin composition according to claim 1, characterized in that Based on 100 parts by weight of the hollow ceramic microspheres, the total amount of the coupling agent and the stearate added is 0.05 to 0.85 parts, preferably 0.15 to 0.65 parts; Preferably, the mass ratio of the coupling agent to the stearate is 1:(0.3-3), more preferably 1:(0.5-2.2).
3. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The coupling agent includes a silane coupling agent and / or a titanate coupling agent; Preferably, the stearate comprises at least one of zinc stearate, calcium stearate or magnesium stearate; Preferably, the average particle size of the hollow ceramic microspheres is 5 to 30 μm; Preferably, the apparent density of the hollow ceramic microspheres is 0.2 to 1.2 g / cm 3 .
4. The thermoplastic resin composition according to any one of claims 1 to 3, characterized in that The acrylonitrile-butadiene-styrene resin material includes acrylonitrile-butadiene-styrene resin, or a mixture of acrylonitrile-styrene copolymer and butadiene-acrylonitrile-styrene graft copolymer; Preferably, at 230° C. and 3.8 kg, the melt flow rate of the polymethyl methacrylate is 1 to 17 g / 10 min.
5. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that The toughening agent includes at least one of acrylonitrile-butadiene-styrene rubber powder, acrylic rubber or silicone rubber; Preferably, the thermoplastic resin composition further comprises 0.5 to 6 parts by weight of other additives; Preferably, the other auxiliary agents include at least one of an antioxidant, a lubricant or a weathering agent.
6. The thermoplastic resin composition according to any one of claims 1 to 5, characterized in that The thermoplastic resin composition comprises, by weight, 10 to 40 parts of acrylonitrile-butadiene-styrene resin material, 30 to 70 parts of polymethyl methacrylate, 1 to 10 parts of modified hollow ceramic microspheres, 1 to 20 parts of a toughening agent, 0.3 to 3 parts of a lubricant, 0.2 to 1.2 parts of an antioxidant and 0.5 to 1.5 parts of a weathering agent.
7. A method for preparing a thermoplastic resin composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate, modified hollow ceramic microbeads and a toughening agent are mixed and extruded to obtain the thermoplastic resin composition.
8. The preparation method according to claim 7, characterized in that: The mixed material also includes at least one of a lubricant, an antioxidant or a weathering agent; Preferably, the mixing comprises premixing acrylonitrile-butadiene-styrene resin material, polymethyl methacrylate and toughening agent and optional antioxidant and 40-60% of lubricant in formula amount, and then adding modified hollow ceramic microspheres and remaining lubricant for mixing; Preferably, the extrusion temperature is 200-260° C., the rotation speed is 300-500 rpm, and the pressure is 1-5 MPa.
9. A mahjong tile shell, characterized in that: The material of the mahjong tile shell comprises the thermoplastic resin composition according to any one of claims 1 to 6.
10. A mahjong tile, characterized in that: The mahjong tiles include the thermoplastic resin composition according to any one of claims 1 to 6 or the mahjong tile shell according to claim 9.
Citation Information
Patent Citations
Preparation method of glass bead / PMMA composite material
CN106700373A
Lightweight composites containing cenospheres and a cementing agent or thermoplastic polymer
GB2348875A
Resin composition and molded article of the same
JP2023094527A
Cited By
Abnormal-sound-proof low-noise ABS (acrylonitrile butadiene styrene) and preparation method thereof
CN120888156A
Infusion bag of compound mannitol injection and preparation method of infusion bag
CN120966227A
Modified ABS composite material as well as preparation method and application thereof
CN121271106A